2017
DOI: 10.12659/msm.900383
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Worsening of Acute Pancreatitis in Patients Admitted with Mild Acute Pancreatitis

Abstract: BackgroundThe aim of the present study was to investigate risk factors for developing more severe pancreatitis, including moderately severe (MSAP) and severe acute pancreatitis (SAP), in patients admitted with mild acute pancreatitis (MAP).Material/MethodsPatients admitted with MAP to our hospital from March 2013 to May 2016 were included and prospectively evaluated. Possible risk factors for developing MSAP or SAP were age, blood glucose level on admission, etiology, sex, Ranson score, amylase level, Acute Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
1
10
2
2
Order By: Relevance
“…Some studies have also reported that different surgical methods directly affect the prognosis of patients (25)(26)(27). A recent study has confirmed that the prognosis of patients with SAP also needs long-term monitoring of serum inflammatory factors (28). The present study focused on the clinical efficacy of duodenoscopy combined with laparoscopy in the treatment of patients with SAP and PP.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have also reported that different surgical methods directly affect the prognosis of patients (25)(26)(27). A recent study has confirmed that the prognosis of patients with SAP also needs long-term monitoring of serum inflammatory factors (28). The present study focused on the clinical efficacy of duodenoscopy combined with laparoscopy in the treatment of patients with SAP and PP.…”
Section: Discussionmentioning
confidence: 89%
“…It is a long-lasting condition shows impact on the physical health and well-being of people. The risk factors associated are gallstones, alcohol, trauma, infections, hypercalcemia, and hypertriglyceridemia [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is a common emergency. AP patients suffer from inflammatory responses such as bleeding, edema and necrosis caused by pancreatic tissue digestion due to abnormally activated pancreatic trypsin resulting from various factors such as drinking, overeating, hyperlipidemia and cholelithiasis ( 1 , 2 ). The clinical manifestations of AP patients are acute and persistent abdominal pains, accompanied with clinical symptoms including nausea, vomiting, fever and stop of flatus and defecation in most patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%